Vanadium(iv/v)-p-dioxolene temperature induced electron transfer associated with ligation/deligation of solvent molecules - Drouza, Chryssoula; Vlasiou, Manos; Keramidas, Anastasios D. (My University, 2013)
Reaction of an aqueous solution of NaVO3 or a methanol solution of [VO(acac)2] with 2,5-bis((bis(2-hydroxyethyl)amino)methyl) hydroquinone, H6bdeah, results in the formation of two major vanadium species characterized by X-ray crystallography: the [(V5+O) 2(bdeah)] and the [(V4.5+O)2(bdeas)S 2] (S = DMSO or MeOH). The vanadium ions in the two species have a trigonal pyramidal and an octahedral coordination sphere respectively. Variable temperature UV-Vis and 51V NMR spectroscopy as well as EPR and electrochemistry showed a temperature induced electron transfer. The diamagnetic [(V5+O)2(bdeah)] is the main species at high temperature. At low temperature one electron is transferred from the bdeah6- to the two vanadium centers resulting in the [(V4.5+O) 2(bdeas)S2] species [H5bdeas = 2,5-bis((bis(2-hydroxyethyl)amino)methyl)-1,4-semiquinone]. The thermodynamic parameters of this intramolecular electron transfer were calculated by UV-Vis (ΔH = -36 ± 2 kJ mol-1 and ΔS = -129 ± 5 J mol-1 K-1) and 51V NMR spectroscopy (ΔH = -37 ± 2 kJ mol-1 and ΔS = -109 ± 5 J mol -1 K-1). The electron transfer is a result of the large change of entropy which is associated with the ligation of the solvent molecules and the geometry change. EPR spectroscopy shows that most of the electron density in [(V4.5+O)2(bdeas)S2] is mainly located on the two vanadium ions.
Keywords: Electron transitions; Nuclear magnetic resonance spectroscopy; Temperature; X ray crystallography